Analysis of the developmental potential of artisanal and small-scale mining: a strategy for South Africa - Twala, Pontsho Francinah (My University, 2024)
The mining industry remains central to the socio-economic development of mineral economies. While this is the case, most African countries have been struggling to translate the benefits of mining into positive developmental outcomes. This has been attributed to several factors including the failure to leverage opportunities from the Artisanal and Small-Scale Mining (ASM) sector which has been growing in most countries. As is the case in other African countries, the mining industry continues to play a considerable role in South Africa’s economy. The industry is expected to contribute significantly to the country’s socio-economic agenda which aims to eradicate poverty and inequality by 2030. Despite the positive outlook, the performance of the industry has been declining resulting in the government identifying a series of interventions aimed at reviving the industry’s activities. Amongst these is the formalisation of the ASM which has been earmarked for job creation and poverty alleviation. The objectives of the Thesis were to establish the developmental potential of ASM in the country, and subsequently develop a strategy framework aimed at enabling the sector to contribute to the mining industry and national development plan. The study was conducted using multiple case studies with data collected and analysed using multiple methods. The major finding from the study is that the ASM sector has the potential to contribute towards the country’s development priorities. This is taken from the evidence that shows a direct link between the sector’s activities and the country’s socio-economic landscape. It was established that the main drivers of ASM are socio-economic challenges in the country, mainly growing unemployment and poverty levels. To this end, ASM is playing a role in providing livelihoods to country’s population is that most affected by poverty and unemployment. As a livelihood strategy, ASM has improved the poverty status as well as the living standards of those that participate in its activities. The evidence from the study revealed that most of the miners measure above the country’s subsistence level and can provide for themselves and their families. The benefits of the sector also extend to communities and overall, these can be linked to several objectives as captured in the country’s development plan. The conclusion from the study is that the developmental potential of ASM can only be leveraged if the challenges in the sector are addressed, and these encompass issues relating to the regulation of the sector, mining land and mineral resources; value chain constraints, and related support, responsible practices, institutional arrangements, and ASM stakeholder relationships.
A thesis submitted in fulfilment of the requirement for the degree Doctor of Philosophy to the Faculty of Engineering and the Built Environment, School of Mining Engineering, University of the Witwatersrand, Johannesburg, 2023
Keywords: Artisanal and small-scale mining; National development plan; South Africa